Brush DC Geared Servomotor Control with Microcontroller. Issue 1 (June 2021) - Syafruddin, R; Lilikwatil, Yakob; Hidayat, Rahmad; Lestari, Ninik Sri; Mahardika, Andrew Ghea; Ramady, Devira Givy
Abstract: The background of this research is to make it easier for young researchers to develop brush control dc geared servomotor with a microcontroller which is part of the overall control system where there are other control parts such as TX commands obtained from sensor devices received through radio communication, conditioning circuits, and transisitor-taransistor logic for the driver for servo-control and other control parts of the bridge brushed dc geared servomotor switching system. Here the research limits itself to the control parts of the dc geared servomotor brush, the control part is in the form of software related to the microcontroller, for the other three parts are discussed in another reset. This limitation only discusses signals from radio, encoder one, encoder two, encoder three, mathematical processing, output command output. The command output is ready to connect to the brush geared dc servomotor.